2020
DOI: 10.20961/lar.v18i2.42997
|View full text |Cite
|
Sign up to set email alerts
|

Kajian inovasi pemanfaatan hasil ikutan tanaman sawit untuk meningkatkan produksi sapi lokal di Kabupaten Aceh Tamiang

Abstract: Kajian tentang inovasi pemanfaatan hasil ikutan sawit bertujuan untuk meningkatkan produksi sapi lokal di Kabupaten Aceh Tamiang. Metode: Sapi yang digunakan sebanyak 15 ekor sapi jantan untuk penggemukan dengan tiga perlakuan, yakni: P1 = Rumput lokal 70 % + konsentrat 30%, P2 = Silase jagung 35% + silase pelepah sawit 35% + indigofera 30% dan P3 = Silase jagung 40% + silase pelepah sawit 30% + indigofera 30%. Pengamatan dilakukan selama 4 bulan dengan masa adaptasi 2 minggu. Teknik pengambilan sampel respond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The results of a previous study conducted in Aceh Tamiang District, namely the use of palm oil waste in local cattle and Brahman cattle showed that provision of frond silage + concentrate was able to increase daily live weight gain of 0.34 kg/cattle/day [13] and 0.99 kg/cattle/day of Brahman cattle [14]. This showed that the provision of agricultural waste increases the livestock population.…”
Section: The Potential Of Feed To Increase Animal Populationmentioning
confidence: 89%
“…The results of a previous study conducted in Aceh Tamiang District, namely the use of palm oil waste in local cattle and Brahman cattle showed that provision of frond silage + concentrate was able to increase daily live weight gain of 0.34 kg/cattle/day [13] and 0.99 kg/cattle/day of Brahman cattle [14]. This showed that the provision of agricultural waste increases the livestock population.…”
Section: The Potential Of Feed To Increase Animal Populationmentioning
confidence: 89%
“…The productivity of the beef cattle business is still low. This is due to the management pattern of raising livestock that is less focused, where breeders have not optimally paid attention to feeding quality and recommended maintenance procedures [9]. Breeders in Aceh Tamiang Regency in providing feed combined with several types that are around the site.…”
Section: Type Of Feed Given As Animal Feedmentioning
confidence: 99%
“…The results show that it provided a similar effect to grass-feeding when supplemented with mineral S and P and cassava leaves [34][35]. Meanwhile, provision of frond silage + concentrate was able to increase daily live weight gain of 0,34 kg/cattle/day [36] and 0,99 kg/cattle/day at Brahman cattle [37].…”
Section: Conditions and Potency Of Oil Palm Plantationmentioning
confidence: 99%